Design of Analytical Balance for Calibration of Measuring Cup of Observatory Type Rain Gauge with Automatic Pump - Muhammad Wildan Abdulmajid; Kerista Tarigan; Syahrul Humaidi; Marhaposan Situmorang; Perdinan Sinuhaji; Yahya Darmawan (IKIP Mataram, 2023)
The Observation type rain gauge is a manual type rain gauge that requires a measuring cup to measure rainfall in millimeters (mm) of rain. Precise measurement requires calibration of the measuring cup so that the scale reading on the measuring cup can be trusted. Calibration of measuring cups using the mass method related to volume can use an analytical balance. Technological developments can make manual analytical balance calibration automatic by utilizing microcontrollers and pumps in filling the volume. The design of the analytical balance gets results where the average correction value for the 50 ml set point is 0.001ml, the 100 ml set point is -0.760 ml, the 150 ml set point is -0.024 ml, the 200 ml set point is -0.739 ml, and the 250 ml set point is 0.628 ml. The uncertainty value for all set points is ±0.58 ml. The correction value at each set point is different, this is influenced by the value of the measuring cup meniscus, water temperature, and Load Cell sensor. The data generated by the tool can be downloaded through the Arduino IDE application and produced files in Excel.